Israel Journal of Health Policy Research - Israeli, Avi.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Israel Journal of Health Policy Research seeks to promote intensive intellectual interactions among scholars and practitioners from Israel and other countries regarding all aspects of health policy, health services research, public health, health promotion, health economics, health care management, and the ethics, sociology, and political science of health care in Israel. The ultimate aim of these intellectual interactions is to contribute to the development of health policy in Israel and around the world. The Israeli health care system is considered to be among the most innovative, advanced, and efficient in the world, and accordingly generates a great deal of scholarly interest and activity. The quantity, quality, and sophistication of Israeli health services research is unusually impressive relative to the number of professionals in the field. This journal seeks to disseminate information about the achievements and dilemmas of Israeli health care, to facilitate dialogue between experts from Israel and elsewhere, and to enhance the extent to which Israel and other countries can learn from one another's health systems. Article selection is guided by considerations of scientific merit and potential contribution to Israeli health care and health systems around the world. Thus, the typical article will report on a new study regarding an important feature of Israeli health care and explore the implications of the study's finding for Israel as well as other countries. The journal also has a particular interest in comparative studies involving Israel and other countries and in-depth, comparative, analyses of Israeli data from multi-national studies. One of the major tools for advancing the journal's objectives is the use of short commentaries by leading scholars, many of whom are from other countries, who are asked to highlight the international significance of an Israeli study's findings and/or methods. The journal gratefully acknowledges the willingness of the European Observatory of Health Care Systems and Policies to assist in identifying relevant international scholars for these commentaries. Another major tool for encouraging cross-national learning is the publication of occasional book reviews, which explore the relevance for Israeli health care of important new books by leading international scholars. The journal also encourages collaborations between authors from Israel and abroad. These can be particularly valuable in papers that integrate information from a variety of sources to address a pressing issue in Israeli health care. The journal features thematic series (the online analogue of special issues) focused on prominent features of Israeli health care that have generated substantial international interest, such as prioritization of new technologies, quality monitoring, health informatics, and IT, addressing the needs of ethnically diverse populations, and reducing health disparities. This will make it possible to examine those issues from varied perspectives and encourage synergy and debate relating to those perspectives. Generally speaking, the number of authors should be limited to four. In cases where there are more than four authors please indicate, in the cover letter, how each author contributed to the manuscript. Pre-submission inquiries may be in Hebrew or English, but must be sent to ijhpr2@gmail.com, all other correspondence must be in English.
Keywords: Public health; Public health administration; Medicine, Preventive; Health promotion; Medical care; Medical policy; Public Health; Health Administration; Health Promotion and Disease Prevention; Health Care; Health Policy